1991
DOI: 10.1002/jemt.1060180403
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of defined sequences of viral RNA and DNA by in situ hybridization of biotinylated DNA probes on sections of herpes simplex virus type 1 infected cells

Abstract: The influence of fixation and enzymatic digestions on the ability of a denatured double-stranded DNA probe to bind specifically to related sequences of RNA and DNA in sections of Lowicryl embedded cells was investigated. Specificity of the hybridization was assessed using a biotinylated cloned subgenomic herpes simplex virus type 1 DNA fragment to localize viral nucleic acids in sections of infected cells. The probe was detected by anti-biotin antibodies and indirect immunogold labeling. Controls indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
2
11
0
3
Order By: Relevance
“…Hybrids were detected with a goat anti-biotin antibody conjugated to 10-nm gold particles (BBInternational). Detection of DNA requires NaOH treatment of the thin sections before hybridization (Puvion-Dutilleul and Puvion, 1991; Puvion-Dutilleul and Pierron, 1992). This treatment was omitted in all our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Hybrids were detected with a goat anti-biotin antibody conjugated to 10-nm gold particles (BBInternational). Detection of DNA requires NaOH treatment of the thin sections before hybridization (Puvion-Dutilleul and Puvion, 1991; Puvion-Dutilleul and Pierron, 1992). This treatment was omitted in all our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Fixation with glutaraldehyde concentrations higher than 1% has been counter-indicated for specimens subjected to in situ hybridization for electron microscopy (Le Guellec 1998) because of interference with the localization of double-stranded DNA. However, hybridization with single-stranded DNA is possible, especially after proteolytic (enzymatic) digestion (Puvion & Puvion 1991). Indeed, the Proteinase K step increased intensity of the in situ hybridization reaction, suggesting that excessive DNA to protein cross-links had been removed.…”
Section: Discussionmentioning
confidence: 99%
“…A recurring problem with the use of biotinylated probes for in situ hybridization at the light-microscope HIST 25/(~-B level is the presence of endogenous biotin leading to false-positive signal. One report has indicated that this can also be a problem at the ultrastructural level unless proteolytic digestion is performed (Puvion-Dutilleul & Puvion, 1991). Digoxigenin is gaining in popularity as an alternative non-isotopic probe label at the light microscope level, being capable of providing high resolution localization of target sequences with minimal background signal .…”
Section: -2214 9 1993 Chapman and Hallmentioning
confidence: 99%